PEMANFAATAN TEPUNG SORGUM PADA PENGEMBANGAN PRODUK CHEESE TART - Sutriyanti Purwanti2, Qory Nur Christanti (Prosiding Pendidikan Teknik Boga Busana, 2020)
The study aims for 1) estabilish a proper recipe for cheese tart making with sorgum slour substitutions, 2) to tebus the acceptance of cheese tart prodak, 3) in order to study the information of nutrional product. This object searches is the cheese tart with a sorgum. The study metod used on the creation of products are Research and Development (R&D), with medel 4D (define, design, development and disseminate). The 30 panelis of a limited scale and 80 panelis is not trained for this application. The results of the creation of the societe products with sorgum flour products can be prepared as follow : 1) the exad recipes for the cheese tart is with grain of mint with a grain 50%, with baking metode. A by product is using interactive opp, 2) product test scale test results by the results of the overall 3,8 and thus a product is received by society, 3) based on proksimons, nutrics in 100 gr sochart air 3,38%, abu 1,82%, protein 7,71 %, fat 2,5%, hard fiber 5,33%, and suepassing 79,61%. Keywords: Sorgum Flour , Sochart, Uji Proksimat